Pengaruh Perceived Organizational Support dan Employee Engagement terhadap Kinerja Karyawan - Septi Diana; Agus Frianto (UNESA In Collaboration With APSMBI (Aliansi Program Studi dan Bisnis Indonesia), 2021)
This study aims to determine how the effect of perceived organisational support and employee engagement on the performance of employees. This study uses quantitative research with a population of employees at UD. Zacyndo safety shoe factory in Tuban and Mojokerto regency. This study using a sample of 45 employees. Data collection techniques were carried out by collecting primary data through the distribution of online questionnaires and using secondary data collection through documentation of organisational activities/events and other written sources of information as writing reference materials. Data were analysed using multiple regression through SPSS version 24. The result showed that perceived organisational support had a negative and insignificant effect on employee performance, employee engagement had a significant and positive effect on employee performance, and perceived organisational support and employee engagement had a positive and significant effect on employee engagement. UD. Zacyndo may improve POS better by paying attention to employee welfare to produce maximum performance. In addition, improve strong relationships with each employee may help the organisation to achieve the intended goals.